Characterization of humoral and cell mediated immune response following aluminium hydroxide gel adjuvanted foot-and-mouth disease vaccine in cattle - MONIKA, MONIKA; SAWHNEY, S M S; SANYAL, A; VENKATARAMANAN, R; RAMNEEK, RAMNEEK; RANDHAWA, S S; OBEROI, M S (The Indian Journal of Animal Sciences, 2014)
Serum samples were analysed for detection of antibody titres against 4 serotypes of FMD virus by liquid phase blocking sandwich ELISA to characterise humoral response following aluminium hydroxide gel foot-and-mouth disease (FMD) vaccination. Animals (18) were divided into 4 groups depending upon the number of vaccinations received earlier. There was no significant rise in antibody titres in the animals of all the 4 groups at 21 days post vaccination (DPV) as compared to the pre-vaccination antibody titres. At 120 DPV, there was significant increase in the antibody titres in groups 1, 2 and 3 following a natural outbreak of FMD. Animals, 2 each from groups 1 and 3 were clinically affected at 95 DPv. The cell mediated immune response was studied in 4 animals by monitoring the expression of specific cytokine m RNA for IL-2. IFNÎ³ and TNFÎ±. All the 4 animals studied showed expression for only IL-2 and IFNÎ³.